Latitude, cultural complexity and color terminology. [article]. - Condon, Richard G.
This brief report is based on a reanalysis of Bornstein's (1973a) and Berlin and Kay's (1969) color data and examines the validity of psychological and cultural explanations of the linguistics processes of color naming and codification. By using a number of statistical procedures, the authors examine the relative contributions of latitude and cultural complexity to the number of basic color terms present in a language. In addition, the reports investigates which aspects of cultural complexity have the most significant impact upon the codification of basic color terms.